Some Features of Bearing Units’ Development Based on Sliding Friction Pairs for Precision Electrospindles - A. S. Kalinichenko; U. L. Basiniu; E. I. Mardasevich (Наука и техника)
In mechanical engineering, various types of bearing units are used in moving connections and sliding pairs (sliding bearings, guides, bushings) are sufficiently widely used. This allows increasing the stiffness of the units, reducing their dimensions, improving heat dissipation, etc. But there are higher friction losses, probability in the increases of situations in which there is a jamming of friction surfaces for application of sliding friction pairs compared to the rolling bearings. These problems are even more important for application of sliding bearings in precision equipment, which typically operates under temperature and humidity stabilized conditions. The aim of the work is the development of methodological approaches to the creation and rational design and manufacture of sliding friction pairs based on the composite antifriction materials’ coatings for the application in vertical precision program-controlled electrospindles for high-speed machining. Questions of development and manufacturing of friction units for precision electrospindles with high rigidity on the basis of composite materials are considered. It is shown that acceptable cutting speed (750 m/min or more) for the quality standpoint of processing with a diamond-like tool can be achieved by placing the cutting edge of the tool on diameter of 200 mm. As a result, two tasks solved: the rigidity of the electrospindle for ultra-high accuracy of mechanical blade processing is achieved; high smoothness of work is provided, which allows achieving nanometric surface roughness with a decrease of deviations to 1 µm from the middle surface line. It is extremely important for a number of special applications.